Diferensiasi Produk Gula Merah Tebu Menjadi Gula Cair dan Gula Recengan Kombinasi - M. Yasser Yasser; Andi Muhamad Iqbal Akbar Asfar; Andi Muhammad Irfan Taufan Asfar; Marlia Rianti; Eko Budianto (Universitas Islam Nahdlatul Ulama Jepara, 2019)
The community service program aims to solve the problem of sugar cane group in Latellang village, Patimpeng sub-district, South Sulawesi province, about increasing business through product differentiation with a combination of ginger extract and pandan leaf extract. The combination is done to reduce the typical aroma of sugar cane in processed sugar. The distinctive aroma of sugar cane is what causes the lack of consumption of brown sugar from sugar cane, so the selling price is very low compared to brown sugar from sugar palm. The implementation of service includes several stages of preparation, cooking, cooling, and packaging. Through training, partners have been able to process sugar cane sugar into a differentiation product with a combination of ginger extract and pandan leaf extract into liquid sugar and recengan sugar with flavor variants according to the extract added. The selling price is very profitable for partners because liquid sugar can be sold at a price of Rp. 15,000 per bottle (250 ml) and recengan sugar is sold at Rp. 8,000 per pouch (each pouch consists of 6 recengan sugar seeds). This sale is very profitable because brown sugar cane is sold at a price of Rp.10,000 per kg, while to make liquid sugar and recengan sugar, only 500 g of sugar cane is needed. Therefore, this service has succeeded in helping to overcome partner problems and increase partner profits through the differentiation of sugar cane into liquid sugar and recengan sugar with combination.